Analysis of airbnb’s green user emotional characteristics: How do human, geographical, housing, and environmental factors influence green consumption? - Wang, Juying; Wang, Cheng (Frontiers in Environmental Science, 2022)
In the context of the sharing economy, green consumption is becoming a trend. Shared accommodation represented by Airbnb has been extensively studied. Analysis of the emotional characteristics of green users is the key to promoting the sustainable development of Airbnb. The article obtains the online reviews of Airbnb green users, fully considers the deviation caused by the weight of feature words to the sentiment calculation, and combines the sentiment value with the weight value to obtain the comprehensive sentiment value of green users. Then, a spatial comparative analysis of green users' emotional characteristics in Beijing, Shanghai, and Hong Kong in China is carried out. The results show that in Airbnb, green users have a more obvious emotional tendency to human and geographical factors, followed by housing factors, and show a lower tendency to environmental factors. The study provides a new perspective for optimizing the Airbnb scoring system and promoting the sustainable development of the shared accommodation market.